(untitled) (Journal of Economic Research & Business Administration, 2016)
Implementation of strategic priorities and reforms in Kazakhstan are aimed primarily at the development of social and economic institutions of the country. And socio-economic modernization as the coming decades will be the most important direction of Kazakhstan. Today in the world crisis of production factors and international policies adversely affect many States. Kazakhstan’s economy will achieve good results in the future if successfully implementing structural reform of the market economy. The development and establishment of market economy in our country has long been the focus of activity of any enterprise meeting the needs and requirements of the buyers. All firms, not realized in time the priority of this production, are unable to resist in today’s competitive environment. In this regard, the present article describes peculiarities of socio-economic modernization. Also, the article discusses the experience of foreign countries for study and use in practice the principles and techniques of economic development, recommendations for the development of enterprise strategies.